Menopause Delays the Typical Recovery of Pre-Exercise Hepcidin Levels after High-Intensity Interval Running Exercise in Endurance-Trained Women - Alfaro-Magallanes, Víctor M. (Nutrients, 2020)
Menopause commonly presents the gradual accumulation of iron in the body over the years, which is a risk factor for diseases such as cancer, osteoporosis, or cardiovascular diseases. Running exercise is known to acutely increase hepcidin levels, which reduces iron absorption and recycling. As this fact has not been studied in postmenopausal women, this study investigated the hepcidin response to running exercise in this population. Thirteen endurance-trained postmenopausal women (age: 51.5 ± 3.89 years; height: 161.8 ± 4.9 cm; body mass: 55.9 ± 3.6 kg; body fat: 24.7 ± 4.2%; peak oxygen consumption: 42.4 ± 4.0 mL·min(−1)·kg(−1)) performed a high-intensity interval running protocol, which consisted of 8 × 3 min bouts at 85% of the maximal aerobic speed with 90-s recovery. Blood samples were collected pre-exercise, 0, 3, and 24 h post-exercise. As expected, hepcidin exhibited higher values at 3 h post-exercise (3.69 ± 3.38 nmol/L), but also at 24 h post-exercise (3.25 ± 3.61 nmol/L), in comparison with pre-exercise (1.77 ± 1.74 nmol/L; p = 0.023 and p = 0.020, respectively) and 0 h post-exercise (2.05 ± 2.00 nmol/L; p = 0.021 and p = 0.032, respectively) concentrations. These differences were preceded by a significant increment of interleukin-6 at 0 h post-exercise (3.41 ± 1.60 pg/mL) compared to pre-exercise (1.65 ± 0.48 pg/m, p = 0.003), 3 h (1.50 ± 0.00 pg/mL, p = 0.002) and 24 h post-exercise (1.52 ± 0.07 pg/mL, p = 0.001). Hepcidin peaked at 3 h post-exercise as the literature described for premenopausal women but does not seem to be fully recovered to pre-exercise levels within 24 h post-exercise, as it would be expected. This suggests a slower recovery of basal hepcidin levels in postmenopausal women, suggesting interesting applications in order to modify iron homeostasis as appropriate, such as the prevention of iron accumulation or proper timing of iron supplementation.